2013
DOI: 10.1017/s1751731113001730
|View full text |Cite
|
Sign up to set email alerts
|

In situ ruminal degradation of amino acids and in vitro protein digestibility of undegraded CP of dried distillers’ grains with solubles from European ethanol plants

Abstract: The objectives of this study were to compare the in situ ruminal degradation of CP and amino acids (AAs) of dried distillers' grains with solubles (DDGS), and to estimate intestinal digestibility (ID) of undegradable crude protein (UDP) with the in vitro pepsinpancreatin solubility of CP (PPS), using either DDGS samples (DDGS-s) or DDGS residues (DDGS-r) obtained after 16 h ruminal incubation. Thirteen samples originating from wheat, corn, barley and blends were studied. Lysine and methionine content of DDGS-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The influences of inclusion of DDGS in the diets of ruminants were not consistent with results of existing studies. Tanaka et al [15] and Westreicher-Kristen et al [16] reported similar DM intake when DDGS was fed to dairy cows at levels of more than 200 g/kg of dietary DM or at levels of 100 or 150 g/kg DM, as reported by Leonardi et al [17], when fed to lambs at levels of 75 and 150 g/kg DM [2] or when fed to ewes at 200 and 300 g/kg DM [1]. Conversely, Janicek et al [18] reported an increase in DM intake when dairy cows where fed DDGS at levels of 0, 100, 200, and 300 g/kg DM.…”
Section: Discussionmentioning
confidence: 99%
“…The influences of inclusion of DDGS in the diets of ruminants were not consistent with results of existing studies. Tanaka et al [15] and Westreicher-Kristen et al [16] reported similar DM intake when DDGS was fed to dairy cows at levels of more than 200 g/kg of dietary DM or at levels of 100 or 150 g/kg DM, as reported by Leonardi et al [17], when fed to lambs at levels of 75 and 150 g/kg DM [2] or when fed to ewes at 200 and 300 g/kg DM [1]. Conversely, Janicek et al [18] reported an increase in DM intake when dairy cows where fed DDGS at levels of 0, 100, 200, and 300 g/kg DM.…”
Section: Discussionmentioning
confidence: 99%
“…This incubation time was chosen as a universal standard that represents a rumen outflow rate of 6.3%/hr which corresponds to a feeding level of approximately 2.5 × maintenance (AFRC, ). Incubations followed the procedure described by Westreicher‐Kristen, Steingass, and Rodehutscord (), using four nylon bags per ration for the determination of zero time disappearance (0 hr) and ten nylon bags per ration and heifer for ruminal incubation.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, in the current study, it was not possible to differentiate whether the reduced milk protein concentration was caused by reduced MCP synthesis alone (based on PD excretion) or in combination with reduced RUP flow to the intestine. Additionally, because the intestinal digestibility of the RUP fraction is a prerequisite for calculating the AA supply to the cow (Westreicher-Kristen et al, 2013), this should be considered as a possible influence on the supply of available protein for milk protein synthesis. Therefore, this possible RUP effect remains unsolved and needs further research.…”
Section: Milk Yield and Milk Compositionmentioning
confidence: 99%